Review concludes that specific recommendations are needed to harmonise the provision of fresh mother's milk to their preterm infants. (8th March 2018) - Picaud, JC; Buffin, R; Gremmo‐Feger, G; Rigo, J; Putet, G; Casper, C; ,
Abstract: Aim: There are no specific recommendations for using a mother's fresh milk for her preterm infant. We reviewed the available evidence on its collection, storage and administration. Methods: The working group of the French Neonatal Society on fresh human milk use in preterm infants searched the MEDLINE database and Cochrane Library up to June 2017 for papers published in English or French. They specifically analysed 282 papers providing information on prospective, retrospective and clinical studies and examined guidelines from various countries. Results: The review concluded that fresh mother's own milk should be favoured in accordance with the latest recommendations. However, it must be carried out under stringent conditions so that the expected benefits are not offset by risks related to different practices. The working group has summarised the best conditions for feeding preterm infants with human milk, balancing high nutritional and immunological quality with adequate virological and bacteriological safety. Professionals must provide parents with the necessary conditions to establish breastfeeding, together with specific and strong support. Conclusion: Based on their review, the working group has made specific recommendations for using fresh mother's own milk under careful conditions, so that the expected benefits are not offset by risks related to practices.